Stability of internal fixation systems based on different subtypes of Schatzker II fracture of the tibial plateau: A finite element analysis - Zeng, Chuyang; Ren, Xiaomeng; Xu, Cheng; Hu, Mengmeng; Li, Jiantao; Zhang, Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Schaztker II fracture is the most common type of the tibial plateau fractures (TPF).There has been a large number of cadaveric biomechanical studies and finite element simulation studies to explore the most stable fixation methods for this type of fracture,which were based on a single fracture morphology.But differences among fracture morphologies could directly affect the stability of internal fixation systems. In this sense, we verified the stability of existing internal fixation modalities by simulating Schatzker II fractures with different fracture morphologies. Objectives:To compare the stability of different filler types combined with locked compression plate/screw in different subtypes of Schatzker II TPF. Methods:Four subtypes of Schatzker II were created based on 3D map of TPF.Each of the subtypes was fixed with LCP/screw or LCP/screw combined with different fill types.Stress distribution,displacement distribution,and the load sharing capacity of the filler were assessed by applying the maximum load during gait.In addition,repeated fracture risks of depressed fragment were evaluated regarding to the ultimate strain of bone. Results:The stress concentration of the implant in each scenario was located on the screw at the contact site between the plate and the screw,and the filler of the defect site significantly reduced the stress concentration of the implant (Subtype A: Blank group 402.0MPa VS Experimental group 315.2 ± 5.5MPa;Subtype C:Blank group 385.0MPa VS Experimental group 322.7 ± 12.1MPa).Displacement field analysis showed that filler significantly reduced the reduction loss of the depressed fragment (Subtype A:Blank group 0.1949mm VS Experimental group 0.174±0.001mm;Subtype C: 0.264mm VS 0.253±0.002mm).Maximum strain was in subtype C with the value of 2.3%±0.1% indicating the greatest possibility of failure risk.And with the increase of its modulus,the bearing capacity of filler increased. Conclusions:The filler of defect site reduce the stress concentration of the implant and the reduction loss of the collapsed block efficiently,thus providing good stability for Schatzker II fracture.In subtype A,the modulus of filler presented the slightest influence on the stability,followed by subtype C,while subtype B was most influenced by the modulus of filler.Therefore,it is necessary to evaluate the preoperative patient imaging data adequately to select the appropriate stiffness of the filler.